EDUKASI ADMINISTRASI POSYANDU DAN MANAJEMEN RUJUKAN PASIEN KE FASILITAS KESEHATAN - Yolanda Ngabito; Desi Novitasari (LPPM Universitas Bina Mandiri Gorontalo, 2025)
This community service aims to improve the understanding of posyandu cadres and the community about posyandu administration and patient referral management to health facilities. The activity carried out in Molotabu Village on November 23, 2024 included education on posyandu administration and the referral process, as well as free health checks. The results of the activity showed an increase in participant understanding and efficiency in the patient referral process. In addition, this activity strengthened the relationship between the community and health facilities, encouraging better access to health services. This service also contributed to improving the quality of posyandu services through direct training and improving the practical skills of posyandu cadres.